(untitled) (Agrotrop : Journal on Agriculture Science, 2026)
The decline in peanut production occurs due to the lack of effective cultivation techniques. This study aims to improve cultivation techniques by utilizing mulch. The study was conducted from April to June 2025, peanut using the Gajah variety. Parameters measured included plant height, number of leaves, total weight of peanut plants, total number of pods, number of filled pods, number of empty pods, total pod weight, filled pod weight, empty pod weight, and seed weight. A randomized block design with four mulch treatments and three replications was applied. Data were analyzed using analysis of variance (ANOVA) and if there were differences, then tested with the Least Significant Difference (LSD) at a significance level of 5%. The results showed that not all parameters showed significant differences. Banana stem mulch(M1) significantly M1 significantly increased plant height of 29.61 cm, the number of filled pods of 26.50 plant, the weight of filled pods of 65.22 g, the weight of seeds of 36.05 g, and the weight of empty pods of 3.33 g compared with the control. Meanwhile, the use of mulch from Gynura procumbens leaves and black silver plastic mulch resulted in lower growth and yield parameters in peanut plants. This study shows that banana stem mulch has the potential to support the increase in organic peanut production sustainably, because it improves soil conditions and contains nutrients such as nitrogen (N), phosphorus (P), and potassium (K) which are good for growth.